Further evaluation of contingency modeling to increase consumption of nutritive foods in children with autism and food selectivity. (17th August 2021) - Flanagan, JeNell; Penrod, Becky; Silbaugh, Bryant C.
Abstract: Research suggests contingency modeling with differential reinforcement of alternative behavior can increase consumption of nonpreferred foods in some children with feeding problems. The current study further evaluated the effectiveness of this treatment with three children with food selectivity and autism. Participants first observed a positive reinforcement contingency in which the confederate model accessed preferred items and edibles contingent on consuming all of the target foods on their plate. If the participant imitated the model and consumed all of their food, they too received access to the same preferred items and edibles. When this contingency was ineffective for two participants, the confederate and feeder modeled nonremoval of the spoon, which increased consumption for both participants. We conclude with a discussion of potential underlying mechanisms for the effects and future research.